Pengaturan Upaya Perdamaian Oleh Debitor Pailit Setelah Adanya Putusan Pernyataan Pailit: Perspektif Hukum Kepailitan Indonesia - Putra, I Gede Khrisna Dharma; Sudiarawan, Kadek Agus (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The purpose of this study is to explain the legal consequences of the issuance of a bankruptcy declaration decision to a debtor by a commercial court and to explain the arrangement of reconciliation efforts by a bankrupt debtor after a bankruptcy declaration decision: the perspective of Indonesian bankruptcy law. A normative legal research method using a statutory approach and a legal concept analysis approach was employed in this study. The method for gathering legal materials is to do a literature review of primary, secondary, and tertiary legal sources. The data was then qualitatively analyzed before being presented in a descriptive analytical report. The results of this study show that the legal implications of the bankruptcy declaration judgment, namely the loss of the debtor's right to manage and control his assets, as well as the recommended peace, are specifically specified in Articles 144 to 177 UUK - PKPU.